Unveiling Safety Practices and Safety Performance Measurement in Construction: A Bibliometric Analysis - Elkaseh, Alaa A.A.; Zakaria, Rozana; Vighio, Anees Ahmed; Pawłowicz, Joanna A.; Munikanan, Vikneswaran; Khan, Jam Shahzaib; Sahamir, Shaza Rina; Ahmad Shakri, Md Rajuna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study critically addresses the ongoing safety challenges within the construction industry which is known as a sector persistently affected by preventable accidents. The research underscores the importance of rigorous safety performance measurement as a key driver for the continuous improvement of Construction Safety Management (CSM). Utilizing a novel science mapping approach, this comprehensive review examines various research in safety performance measurement, delineating the evolution of Construction Safety Performance (CSP) studies.
Keywords: safety management practices; construction safety performance; safety performance measurement; bibliometric analysis